(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Pesticide exposure remains a significant public health concern in agricultural communities, particularly in rural areas with intensive horticultural activities such as Karo Regency. Limited knowledge, low safety awareness, and inconsistent use of personal protective equipment (PPE) contribute to increased health risks among farmers. This study aims to evaluate the effectiveness of the “Pesticide Risk-Free Village” program in improving tomato farmers’ knowledge and attitudes toward safe pesticide practices through health education, the application of simple technologies, and structured monitoring. A quasi-experimental one-group pretest–posttest design was applied to 50 farmers from two farmer groups. The intervention included education on pesticide hazards, training on proper PPE use, demonstrations of safe mixing and spraying techniques, educational videos, and the distribution of a practical booklet. Supporting technologies introduced during the program consisted of ergonomic PPE, portable cholinesterase testing devices, and locally constructed PPE washing facilities. Monitoring activities involved observations of safe practices, blood pressure checks, cholinesterase testing, and continuous assistance by trained students. The results revealed a significant improvement in both knowledge and attitudes after the intervention. The proportion of farmers with good knowledge increased from 36% to 88%, while those with positive safety attitudes rose from 26% to 84%. Wilcoxon analysis confirmed a significant difference between pretest and posttest scores for knowledge (p = 0.000) and attitudes (p = 0.000), with no reduction in any participant’s score. These findings indicate that structured education combined with simple technologies and ongoing monitoring is effective in enhancing farmers’ readiness to apply safe pesticide practices. The program offers a promising community-based model that can be replicated in other horticultural regions.